Quality of life of children with cerebral palsy: Evidence from Assam, India - Daisy Saikia; Manas Ranjan Pradhan (Elsevier, 2024)
Background: Cerebral palsy (CP) is a common childhood physical disability, which often leads to secondary conditions and affects the quality of life (QOL) of the children suffering from it. This study measures the QOL of children with CP using Children with Cerebral Palsy Quality of Life Questionnaire (CP-QOL) and the factors affecting it. Methods: This cross-sectional study covering 140 purposively chosen caregivers of children with CP aged 4-12 years was conducted in Assam, India, 2023. Subscale scores of CP-QOL were computed to determine the overall QOL score. Cronbach's α assessed the subscales' reliability and interval consistency. Bivariate analysis was conducted to present the socio-demographic variation in QOL, and logistic regression revealed the determinants. Regression model diagnostics were performed, which included the Omnibus test, the Hosmer-Lemeshow test, a classification table showing the model's sensitivity, specificity, and overall accuracy, and a ROC curve displaying the model's overall accuracy in predicting the outcome variable. Results: The overall QOL score was 44.94 ± 16.28. QOL scores varied significantly with children's age, Gross Motor Function Classification System (GMFCS) levels, special school enrolment, mother's education, family structure, and the behaviour of relatives and neighbours. Nearly three-fourths of the caregivers perceived a poor QOL of their children with CP. Children's CP type, GMFCS level, associated conditions, and religion were significantly associated with their QOL. Conclusion: The QOL of children with CP are significantly lower, the primary factor being the GMFCS level. Efforts to educate caregivers and customized policies and programs will help improve CP children's QOL.